Illness behaviour and antibiotic prescription in patients with respiratory tract symptoms - van Duijn, Huug J (Oxford University Press, 2007)
BACKGROUND: Although the vast majority of respiratory tract symptoms are self-limiting, many patients visit their GP for these symptoms and antibiotics are overprescribed. AIM: To explore determinants of patients visiting GPs for recent cough, sore throat, or earache; for being prescribed antibiotics; and for patients' satisfaction with visiting the GP. DESIGN OF THE STUDY: Second Dutch National Survey of General Practice (DNSGP-2) with a health interview and an additional questionnaire. SETTING: A total of 7057 adult patients of 163 GPs in the Netherlands. METHOD: Characteristics of patients and GPs as well as morbidity data were derived from the DNSGP-2 and a health interview. Characteristics of the symptoms, GPs' management and patients' satisfaction were measured by an additional written questionnaire. Data were analysed by means of multivariate logistic regression. RESULTS: About 40% of the responders (n = 1083) reported cough, sore throat, or earache in the 2 weeks preceding the interview and, of them, 250 visited their GP. Of this latter group, 97 patients were prescribed antibiotics. Apart from non-medical reasons, relevant medical factors played an important role in deciding to visit the GP. Smokers and patients with cardiac disease or diabetes mellitus were not especially inclined to see their GP. Smoking behaviour, fever, and views on respiratory tract symptoms and antibiotics of patients and GPs were associated with being prescribed antibiotics. Patients' perception of having been carefully examined was associated with their satisfaction, while receiving antibiotics was not. CONCLUSION: GPs should inform patients with clear elevated risk when to visit their GP in cases of cough, sore throat, or earache. There is still a need for GPs and patients to be better informed about the limited significance of single inflammation signs (for example, fever and green phlegm) as an indication for antibiotics. Careful examination of the patient contributes to patient satisfaction.